Reliability and validity of Polar Team Pro measurements in running at different velocities in an indoor setting - van den Tillaar, Roland; Gaustad Pettersen, Fredrik; Lagestad, Pål (Frontiers in Sports and Active Living, 2023)
The purpose of this study was to test the reliability and validity of measurements made by Polar Team Pro on velocity, acceleration, and distance covered at different intensities in an indoor setting. In two test sessions, 10 women (age 15.7±0.4 years, body mass 61.3± 5.3 kg, body height 1.69 ± 0.07 m) performed 100 m runs at different intensities, ranging from 8 to 18 km/h. The 100 m runs were performed in a rectangle at an indoor facility for team handball. The main findings were that the measurements directly calculated by Polar Team Pro underestimated the running distance and velocity (10-15% from 10 km/h speeds), especially at higher speeds (respectively 15 and 6% at 15 and 18 km/h speeds). Between test days, coefficients of variations were found varying from 4.2 to 12.4%, when measuring with different speeds. However, only a significant difference was found for the two runs at 15 km/h between the two test days. It was concluded that Polar Team Pro underestimated the running distance and velocity when measuring rectangular running at different speeds indoors, especially at higher speeds. This underestimation is probably caused by the inaccuracy of the IMU algorithm that calculates the distances, as body height influenced the distance measurements and thereby the velocity measurements. The variability between the different units is thereby also influenced, causing variable coefficients of variance between the sensors. Test–retest variability was acceptable. Based upon the findings of the present study, practitioners should be cautious when measuring speed and distance under indoors settings using Polar Team Pro Sensors, as these measurements are underestimated with increasing speed.